2023
DOI: 10.5489/cuaj.8390
|View full text |Cite
|
Sign up to set email alerts
|

2023 Canadian Urological Association/ Pediatric Urologists of Canada guideline: Pediatric patients with neurogenic lower urinary tract dysfunction

Michael E. Chua,
Priyank Yadav,
Peter Zhan Tao Wang
et al.

Abstract: Prior to Publication, this guideline underwent review by the cua guidelines committee, exPert external reviewers, and the cua executive board. E338 INTRODUCTION AND BACKGROUNDNeurogenic lower urinary tract dysfunction (NLUTD) refers to abnormal function of the bladder, bladder neck, and/or sphincters associated with any neurologic disorder. 1 Congenital pediatric NLUTD is mainly caused by spinal dysraphism, commonly spina bifida (SB). 2 Pediatric NLUTD is increasingly prevalent in Canada. A populationbased stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 113 publications
0
2
0
Order By: Relevance
“…In comparison, only 8% would continue prophylaxis long‐term 17 . The 2023 guideline published by the Canadian Urological Association and the Paediatric Urologists of Canada recommended that antibiotic prophylaxis should be considered if neurogenic bladder patients have had recurrent or severe UTIs within the last 3–6 months or have had a history of symptomatic UTIs with catheter use 18 …”
Section: The Current Role Of Antibioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, only 8% would continue prophylaxis long‐term 17 . The 2023 guideline published by the Canadian Urological Association and the Paediatric Urologists of Canada recommended that antibiotic prophylaxis should be considered if neurogenic bladder patients have had recurrent or severe UTIs within the last 3–6 months or have had a history of symptomatic UTIs with catheter use 18 …”
Section: The Current Role Of Antibioticsmentioning
confidence: 99%
“…17 The 2023 guideline published by the Canadian Urological Association and the Paediatric Urologists of Canada recommended that antibiotic prophylaxis should be considered if neurogenic bladder patients have had recurrent or severe UTIs within the last 3-6 months or have had a history of symptomatic UTIs with catheter use. 18 Multiple retrospective studies have found that bladder irrigation with gentamicin reduces the risk of developing UTIs. One study of 16 adult patients with neurogenic bladder and recurrent UTIs while performing CIC found that 87.5% of patients were UTI-free during the study, while the remaining two patients had a reduction of 50% in the frequency of their UTIs.…”
Section: The Current Role Of Antibioticsmentioning
confidence: 99%